2017
DOI: 10.3390/ijms18112473
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 Stimulates Homologous Recombination Repair of DNA Double-Strand Breaks in a Rad51-Dependent Manner

Abstract: Akt1 is known to promote non-homologous end-joining (NHEJ)-mediated DNA double-strand break (DSB) repair by stimulation of DNA-PKcs. In the present study, we investigated the effect of Akt1 on homologous recombination (HR)-dependent repair of radiation-induced DSBs in non-small cell lung cancer (NSCLC) cells A549 and H460. Akt1-knockdown (Akt1-KD) significantly reduced Rad51 protein level, Rad51 foci formation and its colocalization with γH2AX foci after irradiation. Moreover, Akt1-KD decreased clonogenicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 77 publications
(151 reference statements)
3
37
0
Order By: Relevance
“…3C). RAD51 is a critical factor in HR repair (29,30). We detected RAD51 in ionizing radiation-induced foci in 293T cells ( Fig.…”
Section: Rsv Promotes Dna Damage Repair Through the Homologous Recombmentioning
confidence: 78%
“…3C). RAD51 is a critical factor in HR repair (29,30). We detected RAD51 in ionizing radiation-induced foci in 293T cells ( Fig.…”
Section: Rsv Promotes Dna Damage Repair Through the Homologous Recombmentioning
confidence: 78%
“…Accumulating evidence indicates a regulatory role of Akt isoforms-especially Akt1 and Akt3 in NHEJ [12][13][14][15]. Akt1 has also been reported to be potentially involved in HR-dependent repair processes [16], however these data conflict with other reports [16][17][18].…”
Section: Introductionmentioning
confidence: 86%
“…Mueck et al [16] indicated that Akt1 promotes HRR by influencing Rad51 protein levels and foci formation. Jia et al [17] reported a negative role of Akt on HRR via the CHK1-Rad51 pathway in BRCA1-deficient cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations